Correlation study of male semen parameters and embryo aneuploidy in preimplantation genetic testing for aneuploidy - Yang, Hongyi; Liu, Yan; Niu, Wenbin; Yang, Zilan; Wang, Yang; Jin, Haixia; Li, Gang (Frontiers in Endocrinology, 2023)
The purpose of this study was to evaluate the influence of abnormal semen parameters on embryo aneuploidy based on single nucleotide polymorphism microarray (SNP array). The embryo quality and embryo aneuploidy rates were compared between different groups which divided by male semen parameters (sperm concentration, motility, morphology, and DFI) according the WHO criteria (2021). A total of 464 blastocysts from 103 PGT-A cycles were analyzed. The total blastocysts chromosome aneuploidy rate was 42.3% (191/452). In the teratozoospermia group, the good-quality embryo and blastocyst formation rate were lower than the normal group（44.4%vs60.7%, P <0.01；33.3%vs43.5%, P <0.05）, The good-quality embryo rate in normal DFI group was significantly higher than high-DFI group (59.0% vs 48.4%, P < 0.05). The blastocyst aneuploidy rate in low sperm concentration group, and high DFI group was no differences between with that in normal sperm concentration and DFI group (47.7%vs 37.8% and 44.7%vs37.8%, P>0.05). The aneuploid rate of blastocyst in teratozoospermic and asthenozoospermia group was significantly higher than that of normal morphology and motility group (50.0%vs34.0% and 46.7%vs33.7%, P<0.05). Our study revealed that Teratozoospermic and high sperm DFI was negatively correlated with good-quality embryo rate. Teratozoospermic and asthenozoospermia increased blastocyst aneuploidy rate. Abnormal semen parameters may affect embryo quality and increase the aneuploidy rate of blastocyst chromosomes, suggesting that in clinical practice of assisted reproduction patients with abnormal semen parameters can be treated in advance to improve sperm quality, so as to reduce the impact on embryo quality and achieve a better pregnancy outcome.